1992
DOI: 10.1097/00004032-199207000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Microdistribution and Microdosimetry of Thorium Deposited in the Liver

Abstract: The distribution of thorium in the liver of a patient 36 y after injection with Thorotrast was examined with autoradiographic and scanning electron microscope backscatter image techniques. Autoradiographic examination of randomly selected histologic sections of the liver showed a total alpha activity calculated at 33.7 Bq g-1, with the highest concentration of alpha activity sequestered in subcapsular scare tissue. Subcapsular scare tissue received 4.8 cGy d-1 of alpha radiation, periportal areas were accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This result is consistent with the reported proportion of hemangiosarcomas among liver cancers attributable to thorotrast irradiation of 21Y28% (Mori et al 1999;van Kaick et al 1991;Andersson 1997), while among atomic bomb survivors the fraction of liver hemangiosarcomas was 0.2Y0.3%. Cholangiocarcinomas arise in the bile ducts, which were estimated to receive 15 times higher exposure than the hepatic cord tissue (Dagle et al 1992). The high proportion of hepatocellular cancer in the present study is consistent with findings for the atomic bomb survivors (Preston et al 2007) but not with studies of Thorotrast exposed patients for which cholangiocarcinoma was found to be the major histological type (UNSCEAR 2008).…”
Section: Discussionsupporting
confidence: 89%
“…This result is consistent with the reported proportion of hemangiosarcomas among liver cancers attributable to thorotrast irradiation of 21Y28% (Mori et al 1999;van Kaick et al 1991;Andersson 1997), while among atomic bomb survivors the fraction of liver hemangiosarcomas was 0.2Y0.3%. Cholangiocarcinomas arise in the bile ducts, which were estimated to receive 15 times higher exposure than the hepatic cord tissue (Dagle et al 1992). The high proportion of hepatocellular cancer in the present study is consistent with findings for the atomic bomb survivors (Preston et al 2007) but not with studies of Thorotrast exposed patients for which cholangiocarcinoma was found to be the major histological type (UNSCEAR 2008).…”
Section: Discussionsupporting
confidence: 89%
“…Patients who were chronically exposed to alpha particles from Thorotrast (contrast material containing colloidal thorium dioxide) (9, 10) and workers at the Mayak nuclear facility who were exposed to both inhaled plutonium and external gamma radiation (8,45,46) had elevated risks for liver cancer. Of note, the dominant histological type is hepatocellular carcinoma among the LSS participants (Table 2) and Mayak workers with relatively lower plutonium doses (46), while it is cholangiocarcinoma and/or hemangiosarcoma among Thorotrast patients, reflecting the fact that intravenously administered Thorostast is more likely to deposit in periportal areas than in hepatic cord areas of the liver (47). In the Mayak workers cohort, hemangiosarcoma was also observed, exclusively among workers exposed to higher plutonium doses (!4 Gy) (46).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the spatial resolution of a gamma camera is insufficient to provide reliable microdosimetry. In a post-mortem autoradiography evaluation of a subject exposed to the alpha emitter 232 Th, microscopic “hot spots” with doses up to 50-fold higher than those assuming a homogeneous organ biodistribution were found [ 36 ]. Therefore the 440 keV gamma images of 213 Bi-DOTATOC are not sufficient for imaging-based dosimetry.…”
Section: Discussionmentioning
confidence: 99%